1993
DOI: 10.1007/bf00199617
|View full text |Cite
|
Sign up to set email alerts
|

Leaf gas exchange of beech (Fagus sylvatica L.) seedlings in lightflecks: effects of fleck length and leaf temperature in leaves grown in deep and partial shade

Abstract: Summary. Responses of leaf gas exchange in shade and half-shade grown seedlings of the European beech, Fagus sylvatica L., to constant light conditions indicate different phases of photosynthetic induction: an immediate, a fast and a subsequent slow phase. The slow phase has both biochemical and stomatal components. The higher the induction, the higher the lightfleck utilization efficiency (LUE) attributable to a lightfleck. LUE can be higher than 100% compared to a theoretical instantaneous response. Lightfle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 48 publications
4
56
0
1
Order By: Relevance
“…Juvenile beech plants in their natural habitat depend strongly on short light flecks for their assimilation (Kuppers & Schneider 1993). Understorey plants typically maintain a relatively high conductance between light flecks (Pearcy & Calkin 1983;Pearcy 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Juvenile beech plants in their natural habitat depend strongly on short light flecks for their assimilation (Kuppers & Schneider 1993). Understorey plants typically maintain a relatively high conductance between light flecks (Pearcy & Calkin 1983;Pearcy 1987).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some studies of lightfleck utilization have suggested that shade leaves may be capable of using sunflecks more efficiently than sun leaves (CHAZDON & PEARCY, 1986b;KÜPPERS & SCHNEIDER, 1993; TANG et al, 1994). This capacity could be related to a significant efficiency in increasing photosynthetic capacity exhibited by shade species in response to increasing light availability (CHOW et al, 1988; TURNBULL, 1991; THOMPSON et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Rubisco, stomatal opening and their maintenance under low-light (CHAZDON, 1988;PEARCY et al, 1994). Previous studies have suggested that shade-tolerant species are more efficient in sunfleck utilization due to the ability to achieve and maintain a high photosynthetic induction state when compared to shade-intolerant species (SCHNEIDER et al, 1993;KÜPPERS et al, 1996). It is a crucial trait since sunflecks contribute with 10-80% of total diurnal photosynthetically active radiation (CHAZDON et al, 1996), being determinant to the carbon gain of plants in understory environments (SIMS & PEARCY, 1993; PEARCY & YANG, 1998).…”
Section: Aclimatação Fotossintéticamentioning
confidence: 99%
See 2 more Smart Citations